Identification of an equivalent viscous damping function depending on engineering demand parameters. (1st June 2019) - Heitz, T.; Giry, C.; Richard, B.; Ragueneau, F.
Highlights: Jacobsen inspired method to assess an equivalent damping ratio after cyclic quasi-static reverse tests. Development of a nonlinear single-degree-of-freedom model describing damage, friction and pinching effect. Digital Image Correlation tool to assess modal displacements. Analysis of the influence of engineering demand parameters on equivalent viscous damping ratio. Formulation of an equation for the dependence of the EVDR on engineering demand parameters. Abstract: When performing a nonlinear time-history analysis of a reinforced concrete structure, it is necessary for the used structural model to dissipate the correct amount of energy. For the sake of computational efficiency, viscous damping models are still commonly used to account, partially or not, for non-viscous dissipations (e.g. friction between the crack surfaces, bond slip at the steel-concrete interface). In order to improve the physical relevance of such a substitution, an evolving equivalent viscous damping ratio estimated for a simply supported reinforced concrete beam is proposed in this paper. This work takes place in the scope of a moderate seismicity context for which steel yielding is not expected. The results are not directly identified from experimental results but rather from numerical simulations carried out thanks to an equivalent single-degree-of-freedom model, itself calibrated by means of quasi-static experiments. To begin with, the experimental setup used to calibrate the single-degree-of-freedom model and the equivalent viscous damping ratio assessment method are presented. Then, the single-degree-of-freedom model and the identification procedure are exposed. The resulting outputs are presented and commented. Finally, numerical experiments are performed in order to obtain equivalent viscous damping ratio values corresponding to a given maximum time-history curvature and a curvature demand.